Disasters, Discourse, and the Digital Sphere: A Critical Discourse Analysis of Natural Disaster Narratives on @NajwaShihab’s YouTube Channel - Khasanah, Hanna Nur; Taufiqur Rahman (Faculty of Ushuluddin and Philosophy, 2023)
This study endeavors to delve into the discourse surrounding natural disasters in Indonesia, as portrayed on the YouTube channel @NajwaShihab, employing the critical discourse analysis framework introduced by Teun A. van Dijk. Van Dijk’s methodology is applied to elucidate the construction of discourse and its ramifications within a broader socio-cultural milieu, facilitating an in-depth exploration of the meanings and social implications inherent within the discourse. Natural disasters represent imminent threats or consequences stemming from natural phenomena, which may be exacerbated by human activity, posing risks to both human life and the environment. Three select videos from the @NajwaShihab YouTube channel serve as the focal point of examination in this study. Utilizing a qualitative descriptive approach, the findings of the analysis unveil a comprehensive portrayal of natural disasters in Indonesia through the lens of Islamic perspectives, employing universally accessible language to engage the audience.